Myeloproliferative diseases as possible risk factor for development of chronic thromboembolic pulmonary hypertension: a genetic study - Eichstaedt, Christina; Benjamin, Nicola; Fischer, Christine; Egenlauf, Benjamin; Harutyunova, Satenik; Xanthouli, Panagiota; Marra, Alberto M.; Hinderhofer, Katrin; Grünig, Ekkehard (International journal of molecular sciences, 2020)
Chronic thromboembolic pulmonary hypertension (CTEPH) is a rare disease which is often caused by recurrent emboli. These are also frequently found in patients with myeloproliferative diseases. While myeloproliferative diseases can be caused by gene defects, the genetic predisposition to CTEPH is largely unexplored. Therefore, the objective of this study was to analyse these genes and further genes involved in pulmonary hypertension in CTEPH patients. A systematic screening was conducted for pathogenic variants using a gene panel based on next generation sequencing. CTEPH was diagnosed according to current guidelines. In this study, out of 40 CTEPH patients 4 (10%) carried pathogenic variants. One patient had a nonsense variant (c.2071A>T p.Lys691*) in the BMPR2 gene and three further patients carried the same pathogenic variant (missense variant, c.1849G>T p.Val617Phe) in the Janus kinase 2 (JAK2) gene. The latter led to a myeloproliferative disease in each patient. The prevalence of this JAK2 variant was significantly higher than expected (p < 0.0001). CTEPH patients may have a genetic predisposition more often than previously thought. The predisposition for myeloproliferative diseases could be an additional risk factor for CTEPH development. Thus, clinical screening for myeloproliferative diseases and genetic testing may be considered also for CTEPH patients.